Implementação do protocolo de comunicação DTN aplicado para cidades inteligentes - Figueiredo, Matheus Ronssani de (2018)
In a Smart City context, collecting and distributing relevant information to provide every type of service is far beyond necessary. To achieve this connectivity the network have to be prepared to sustain a heavy traffic of data with the limitations of communications protocols and physical conditions, as high node mobility and link failure. An approach to this challenge is the DTN (Delay/Disruption Tolerant Networking) architecture, which based in the “bundle” layer in the stack of the protocol to maintain the QoS (Quality of Service) of the communication. This paper focus on evaluating and modeling a DTN version optimized for smart cities communications.